1998
DOI: 10.1046/j.1460-9592.1998.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

A timed reexpansion inspiratory manoeuvre (TRIM) for treating oxyhaemoglobin desaturation in children following a period of apnoea—studies in an animal model

Abstract: Our clinical experience has shown that the use of a constant distending airway pressure of 30 cm water for 10 s, termed a timed reexpansion inspiratory manoeuvre (TRIM), is often successful in correcting oxyhaemoglobin desaturation in anaesthetized children. The aim of this study was to assess the efficacy of TRIM in lambs. Following a standard relaxant anaesthetic, ventilation was stopped and oxyhaemoglobin saturation allowed to fall to 70% and the time taken to return to baseline was compared between three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Lung function of the control group did not return to baseline even at the end of 3 min of normal ventilation, suggesting the development of atelectasis postapnoea. A TRIM with 30% oxygen in nitrous oxide (T1) restores the oxygen saturation quicker to baseline than the control group with normal ventilation alone, confirming results from earlier studies (6). The practice of preoxygenation is also reinforced by our results as the lambs maintained maximal oxygen saturation if they were ventilated with 100% oxygen prior to the 2 min of apnoea, although there is new evidence suggesting that preoxygenation may aggravate atelectasis (5,10).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Lung function of the control group did not return to baseline even at the end of 3 min of normal ventilation, suggesting the development of atelectasis postapnoea. A TRIM with 30% oxygen in nitrous oxide (T1) restores the oxygen saturation quicker to baseline than the control group with normal ventilation alone, confirming results from earlier studies (6). The practice of preoxygenation is also reinforced by our results as the lambs maintained maximal oxygen saturation if they were ventilated with 100% oxygen prior to the 2 min of apnoea, although there is new evidence suggesting that preoxygenation may aggravate atelectasis (5,10).…”
Section: Discussionsupporting
confidence: 81%
“…Since it is not possible to subject children to this type of study, a lamb model was therefore used; however, they suffered no obvious insult and made apparent normal recoveries. We have previously used this model successfully and found that lambs responded in a similar way to anaesthetized patients (6,7). We therefore believe this to be an acceptable model but acknowledge that caution must used in extrapolating our results to human practice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Marcus et al (20) demonstrated that the use of 100% oxygen may worsen pulmonary compliance in children <2 years. MacDonald et al (22) showed that oxygen tension was restored faster in apneic lambs after a volume recruitment maneuver ventilated with 33% oxygen in nitrous oxide compared with 100% oxygen. The benefit of an alveolar volume recruitment manoeuver has been demonstrated in children (20,23).…”
Section: The Respiratory System In Pediatric Anesthesiamentioning
confidence: 99%
“…One of the ten men and one of the eight premenopausal women had mildly elevated (and probably insignificant) prolactin levels. The incidence of PONV is 60-70% with major gynaecological procedures 1 .…”
Section: Sex Hormone Levels In Patients Receiving Long-term Intrathecmentioning
confidence: 99%